Universal Point Sets for Drawing Planar Graphs with Circular Arcs - Angelini, Patrizio; Eppstein, David; Frati, Fabrizio; Kaufmann, Michael; Lazard, Sylvain; Mchedlidze, Tamara; Teillaud, Monique; Wolff, Alexander (Journal of Graph Algorithms and Applications, 2014)
We prove that there exists a set S of n points in the plane such that every n-vertex planar graph G admits a planar drawing in which every vertex of G is placed on a distinct point of S and every edge of G is drawn as a circular arc.